Qualitative study on emotional implications, treatment perception, and survivorship of female breast cancer (Research, Society and Development, 2023)
Introduction: From the diagnosis to the treatment of breast cancer, the patient and her family experience some stages until the acceptance of the disease and adherence to treatment, which are part of the coping process. This study aimed to identify and analyze the coping experienced by users of the public health system who are breast cancer survivors, from their perspectives of diagnosis, emotional implications, perception about treatment and life after cancer treatment, in a reference center in Recife-PE. Methodology: This is a qualitative, descriptive and exploratory study, developed with women diagnosed with breast cancer, through semi-structured interviews. Five women participated in the study. Based on data analysis, it was possible to identify survivors, and the construction of the categories: "the impact of the diagnosis", "coping during treatment" and "changes after diagnosis/treatment", highlighting the main reports. Results: The analysis of the interviews highlighted feelings such as fear, sadness, surprise and even rapid acceptance. Factors such as family support, religiosity and support from the multiprofessional team proved to be indispensable during facing the disease. Conclusion: Women survivors are faced with several concepts, preconceptions, changes in their self-esteem, in the family nucleus, and in the restructuring of their body image. Multiprofessional assistance in oncology is essential, professionals must cooperate beyond technical-scientific knowledge, because it is necessary to welcome, understand and consider the participation of patients in decision making, in order to favor the success of therapy and the fight for life.